1986
DOI: 10.1128/jb.168.2.805-814.1986
|View full text |Cite
|
Sign up to set email alerts
|

Osmotic regulation of transcription: induction of the proU betaine transport gene is dependent on accumulation of intracellular potassium

Abstract: The proU locus, which encodes a high-affinity betaine transport system, and the kdp operon, which encodes a potassium transport system, are the principal osmoresponsive genes in Escherichia coli and Salmonella typhimurium. The kdp operon is known to be induced in response to changes in cell turgor. We have investigated the control of proU expression and shown that it differs from that of kdp in a number of fundamental ways. Rather than responding to changes in turgor, proU expression is principally determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
169
1
1

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 219 publications
(181 citation statements)
references
References 45 publications
(46 reference statements)
5
169
1
1
Order By: Relevance
“…Thus cells grown in 200 mM-NaCl showed negligible increases in internal proline concentration but significant increases in K+ concentration over the same range (Whatmore, 1989). However, if upshock is more substantial, accumulation of K+ will lead to induction and/or activation of proline biosynthetic enzymes, since accumulation of excessive K+ may be potentially deleterious to cellular metabolism (Sutherland et al, 1986;Booth et al, 1988). K+ has now been shown to exert its effects in upshocked enteric bacteria via the induction of glycine betaine uptake (proU-mediated) due to alteration of DNA structure.…”
Section: Discussionmentioning
confidence: 99%
“…Thus cells grown in 200 mM-NaCl showed negligible increases in internal proline concentration but significant increases in K+ concentration over the same range (Whatmore, 1989). However, if upshock is more substantial, accumulation of K+ will lead to induction and/or activation of proline biosynthetic enzymes, since accumulation of excessive K+ may be potentially deleterious to cellular metabolism (Sutherland et al, 1986;Booth et al, 1988). K+ has now been shown to exert its effects in upshocked enteric bacteria via the induction of glycine betaine uptake (proU-mediated) due to alteration of DNA structure.…”
Section: Discussionmentioning
confidence: 99%
“…Control by turgor is supported by the finding that a sudden increase in medium osmolarity, which reduces turgor, transiently turns on kdp-FABC expression. This model has been challenged by the finding that under some conditions expression of kdpFABC is only significantly induced when the osmolarity of the medium is increased by salt and not in case of sugar (9,14,15). Based on kdpD mutants, which give rise to K ϩ -independent kdpFABC expression but regain the ability to respond to changes in medium osmolarity independently of the solute, it is suggested that KdpD senses two stimuli: increase in osmolarity and K ϩ limitation (16).…”
Section: ) (3)mentioning
confidence: 99%
“…Because of difficulties in obtaining kdp mutations in this organism, it has been suggested that there may be an important difference between the properties of the Kdp system in E. coli and in S. typhimurium (17). In this report, we describe the isolation of a kdp-lacZ fusion in S. typhimurium.…”
mentioning
confidence: 96%